(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This article is devoted to the interpretation of the author's deep penetration into the inner world of the hero, a detailed description of the spiritual world of the character, the expression of emotional experiences with the help of a psychological portrait, which is one of the direct visual tools of "artistic psychology".In the psychodynamic portrait type, the image of the hero is characterized not by a detailed image, but by details specific to his appearance and mental state, which changes depending on the requirements of the situation, in the description of events and dialogues.